Millennial paleoclimate variations on the Central Tibetan Plateau during MIS4-MIS2 inferred from a sediment core based RPI chronology - Yang Zhang; Junbo Wang; Shuangwen Yi; Siwei Yu; Jinlei Kai; Yao Gu; Qingfeng Ma; Jianting Ju; Liping Zhu (Scientific Reports)
Abstract Lakes on the Tibetan Plateau, highly sensitive to environmental changes, play a key role in paleoclimatic studies. However, dating limitations often constrain investigations to periods before the Last Glacial Maximum (LGM). Relative paleointensity (RPI) of lake sediments offers a valuable means of developing high-resolution chronological frameworks during the Brunhes Chron. This study presents an RPI record from a lacustrine sediment core (NMC2020-1A) from Nam Co, Tibetan Plateau (TP), based on normalization of natural remanent magnetization (NRM) by anhysteretic remanent magnetization (ARM) over 20–60 mT demagnetization range using the slope method. Rock magnetic analyses indicate pseudo-single domain (PSD (≈vortex) magnetite as the dominant magnetic mineral. Five age control points were identified by correlating the RPI record with the PISO-1500 paleointensity stack. An age model for the 38.71–10.8 m upper section of the core has been established, covering 78 to 25 ka. The environmental magnetic parameter κARM/κ exhibits a clear precession cycle, highlighting the sensitivity of environmental changes on the TP to variations in solar radiation. Furthermore, comparisons of the κARM/κ ratio at the millennial scale with stalagmite and Greenland ice core records demonstrate the influence of high-latitude abrupt climate shifts on the climate of the TP.